Analisis Pengembangan Karier Pegawai Pada Badan Narkotika Nasional (BNN) Kota Gorontalo: Studi pada Badan Narkotika Nasional (BNN) Kota Gorontalo - Robiyati Podungge; Valentina Monoarfa; I Nengah Agus Eka Sanjaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to see how employees' careers develop at the Gorontalo City Narcotics Agency. The research method used in this research is a descriptive qualitative method. The data used is primary data obtained from interviews with 3 informants. Data analysis in this research uses an interactive model, namely data obtained from interviews, field notes and documentation, by organizing data into categories, describing it into units, synthesizing it, arranging it into patterns, choosing what is important and what is important. will be studied, and make conclusions so that they are easily understood by yourself and others. The results of the research show 1) Career development for Gorontalo City BNN employees are given the opportunity to take part in education and training that is appropriate to the scientific field and also the needs of the BNN organization to strengthen the organization and also improve the work skills of employees at Gorontalo City BNN, 2) Employees at City BNN Gorontalo is given the same opportunity and opportunities in the promotion process by paying attention to employee performance based on the regulations that apply to employees which are carried out objectively and transparently by fulfilling a sense of justice in accordance with the criteria and requirements. 3) Key role in employee career development at BNN Gorontalo City is the leader of the organization other than the individual employee himself, and 4) The obstacles faced by the Gorontalo City BNN in developing the career of its employees are limited human resources, opportunities, unclear career paths and limited achievements.